THE ANALYSIS OF PRONUNCIATION ERROR ON ENGLISH DIPHTHONGS MADE BY CERTIFIED TOUR GUIDES - Wulan Wangi; Dzicky Amiq Nudiya (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
As a rule, the tour guides speak English to introduce and describe the tourism object to the foreign tourist. The communication between tour guides and tourists should be worked without any obstruction to avoid misunderstanding. However, the pronunciation error on English diphthongs still occurred when the tour guides spoke English with the tourist. The objectives of this study were 1) analysing the types of pronunciation error on English diphthongs made by certified tour guides, 2) finding the most difficult English diphthongs made by certified tour guides, and 3) identifying the reasons of the pronunciation error on English diphthongs made by certified tour guides. The research method was descriptive qualitative. The researcher used four steps in collecting the data, they were recording, questionnaire, observation, and documentation. The respondents of this research were five certified guides. The research result showed that pronunciation error on English diphthongs made by certified guide was 120 errors (76 errors in substitution and 44 errors in omission). The highest pronunciation error was [??] diphthong and it occurred 45 times. The certified tour guides did not aware that they make pronunciation error. They had conversation in English with the foreign tourist but they had less time in learning pronunciation with native or competent person in English. The certified tour guides need to improve their English quality through learning more about pronunciation with the expert to minimize their pronunciation error on English diphthongs.